Westernized and Diverse Dietary Patterns Are Associated With Overweight-Obesity and Abdominal Obesity in Mexican Adult Men - Rodríguez-Ramírez, Sonia; Martinez-Tapia, Brenda; González-Castell, Dinorah; Cuevas-Nasu, Lucía; Shamah-Levy, Teresa (Frontiers in Nutrition, 2022)
Introduction. The prevalence of overweight and obesity in Mexican adults is very high. To identify the dietary characteristics related with this disorder is necessary to design intervention. The objective was to analyze the association between dietary patterns and obesity in Mexican adults. Materials and Methods. This is a cross-sectional study carried out in Mexican adults (20-59 years old) participating in the Halfway National Health and Nutrition Survey 2016. Participants (n=5735) were classified as having normal weight, overweight-obesity and by their abdominal circumference as having abdominal obesity or not. With information from a seven-day food frequency questionnaire, we used a K-means cluster analysis to derive dietary patterns and calculated a healthy diet indicator to evaluate quality. The association between dietary patterns and overweight-obesity and abdominal obesity was assessed with Poisson regression models adjusted by some characteristics. Results. We identified a Rural pattern characterized by tortilla, legumes and egg consumption; a Diverse pattern, characterized by fruits, meat and poultry, vegetables, and dairy beverages, and desserts; and a Westernized pattern, characterized by sweetened non-dairy beverages, fast food, bakery and cookies, candies and salty snacks. In men, Westernized pattern was associated with overweight-obesity (PR=1.11, 95%CI 0.97-1.27), and abdominal obesity (PR= 1.15, 95%CI 1.00-1.33), the Diverse pattern was associated with overweight-obesity (PR= 1.18, 95%CI 1.00 – 1.38), and abdominal obesity (PR= 1.27, 95%CI 1.07 – 1.50), compared with the Rural pattern. In women, these dietary patterns were not associated with obesity. Discussion: Westernized and Diverse patterns are associated with overweight and obesity and abdominal obesity in men. Gender-specific recommendations and surveillance are necessary in the Mexican adult population.